A model of fault allocation in contract law: Moving from dividing liability to dividing costs - Osnat Jacobi; Avi Weiss (Bar-Ilan University, Department of Economics, 2010)
We consider default rules for instances in which parties to a contract did not allocate the risk of a certain contingency, and both sides could have helped avoid the occurrence of breach of the contract or lessen the damages from it occurring. We compare alternative regimes with a fault-based guideline suggested in the literature for assigning the liability between the parties and discuss the pros and cons of each. We present a new possibility and show how this solves the problems raised by the other solutions. Under this mechanism, the court announces that any party that invests half of the optimal level of precautionary costs, as determined jointly by the parties, is off the hook, and that if each side invests this amount, the damage will be split. We demonstrate that this achieves optimality by leading the parties to jointly determine the optimal level of precautionary costs and to allocate the steps to be taken to the low cost bearer.
Keywords: K12; 330; Contract Law; Breach of Contract; Unallocated Risk; Strict Liability Regime; Fault Regime